SPECIFIC MARKETING STUDIES OF ASSORTMENT OF DIURETIC DRUGS IN PYATIGORSK PHARMACIES - E. V. Kleychuk; S. A. Mikhaylova; L. A. Zolotukhina; N. A. Andreeva; E. A. Popova; O. G. Ivchenko (Фармация и фармакология (Пятигорск))
Diuretics are ones of the most popular classes of antihypertensive remedies. They are characterized by low cost, high efficiency, and a good acceptability. Therefore the purpose of the research was to study an assortment of diuretics and to develop merchandise inventory of a pharmacy organization to improve quality of population drug supply. During the research we used methods of system, economic and statistic analysis, questioning, content-analysis and ABCanalysis. The research resulted on three groups of diuretic remedies depending on the specific density in general revenues from realization of these drugs group A. Group B amounted to 29.3% of the turnover. The rest 13 names were included in a Group C, their share was 29.4% of an amount of diuretics drugs. Pharmacy should always have drugs from the groups A and B.